Implicit numerical method for discharging of energy storage curved container in appearance of nanomaterial evaluating performance. (April 2023) - Abu-Hamdeh, Nidal H.; AlQemlas, Turki; Talabany, Ziyad Jamil; Rothan, Yahya Ali; Milyani, Ahmad H.; Elamin, Abd Elmotaleb A.M.A.
Abstract: The performance of the system during discharging has been improved in this article involving nano-sized powders. The shapes and concentrations of powders have been supposed as parameters in simulation. To derive the equations, properties of nanomaterial were predicted based on homogeneous mixture and the impact of velocity has been neglected. Galerkin technique for finding the answer of the problem was hired incorporating implicit approach for unsteady terms. Both variables have favorable efficacy on freezing and make the freezing quicker. Time of process declines with an augmenting ϕ and shape factor more than 26 % and 7 % which means that concentration has more sensible efficacy. The minimum time of discharging is 236.77 s which happens if maximum concentrations of powders with greater shape factor have been applied. Highlights: The performance of system during discharging has been improved. Time of process declines with augmenting ϕ around 26 %. Freezing time decreases with increasing shape factor about 7 %. The minimum time of discharging is 236.77 s.